Health Action Process Approach (HAPA) as a Framework to Understand Compliance Issues With Health Protocols Among People Undergoing Isolation at Emergency Hospital for COVID-19 Wisma Atlet Kemayoran and RSCM Kiara Ultimate Jakarta Indonesia - Malik, Khamelia; Amir, Nurmiati; Kusumawardhani, A. A. A. A.; Lukman, Petrin Redayani; Karnovinanda, Rhapsody; Melisa, Leslie; Dewi, Lidya Purnama; Lasmono, Agnes (Frontiers in Psychiatry, 2022)
Introduction: This study aims to identify the psychosocial determinants and examine the mediation mechanisms of the compliance with COVID-19 health protocols among people undergoing isolation in health facilities that specifically treat COVID-19 cases in Jakarta, Indonesia. Methods: This is a cross-sectional study which used socio-cognitive approach, known as the Health Action Process Approach (HAPA), to understand the complexity of issues related to compliance with health protocols. A total of 1,584 subjects participated in this study, including 865 men and 719 women over the age of 18 years old during the data collection period (October 19-26, 2020). The data were collected using questionnaire that was developed by a team of experts from the Faculty of Medicine, Universitas Indonesia – Dr. Cipto Mangunkusumo General Hospital, and survivors. The data that has been collected were then analyzed using Structural Equation Modeling, a multivariate data analysis technique. Results: The final research model in this study fulfills the criteria for a good model fit. This study found that individuals who have strong self-efficacy regarding their ability to implement behaviors and overcome obstacles will have stronger intent to comply in the future. The study also found that stronger intent will lead to stronger planning, and planning was found mediating intention and compliance with health protocols. Conclusion: This research model is comprehensive and useful in understanding compliance with health protocols among people undergoing isolation in health facilities for COVID-19 (Wisma Atlet and RSCM Kiara Ultimate). Having intent (related to the risk perception, outcome expectancies, and self-efficacy) and having a plan can positively influence the behavior of people undergoing isolation, resulting in better compliance to health protocols. The understanding gained from this study can be used to improve strategies related to compliance with health protocols against Covid-19 in the communities.